2011
DOI: 10.1111/j.1399-3038.2011.01227.x
|View full text |Cite
|
Sign up to set email alerts
|

Asthma, atopy and exhaled nitric oxide in a cohort of 6‐yr‐old New Zealand children

Abstract: Airway inflammation as measured by exhaled nitric oxide in young New Zealand children is related to their level of specific IgE to aeroallergens. This has implications for the utility of nitric oxide as a diagnostic and management tool in childhood asthma and for the importance of specific IgE as a marker of asthma severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
3
10
0
3
Order By: Relevance
“…Studies have shown that FeNO levels are raised in atopic subjects, regardless of whether or not they have significant lower respiratory tract symptoms [5, 12, 13]. Studies of multiple birth cohorts of asthmatic and atopic patients found that only atopic asthmatics had an elevation in FeNO and that nonatopic asthmatics had relatively normal levels [5, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that FeNO levels are raised in atopic subjects, regardless of whether or not they have significant lower respiratory tract symptoms [5, 12, 13]. Studies of multiple birth cohorts of asthmatic and atopic patients found that only atopic asthmatics had an elevation in FeNO and that nonatopic asthmatics had relatively normal levels [5, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to some studies that have demonstrated that sensitization to specific allergens such as dust mite are major determinants of increased FeNO in children. 6 Our study highlights the importance of rat allergen sensitization as well and the dose-response relationship of polysensitization and airway inflammation.…”
mentioning
confidence: 74%
“…Varios autores han determinado el impacto de asma y atopia en los niveles de ONe [8][9][10][11][12][13][14][15] . Tanto asma como atopia por separado presentaron en general aumentos en ONe mayores a 20%, llegando incluso a triplicar los valores en algunas ocasiones.…”
Section: Discussionunclassified
“…Además, se reportan niveles significativamente más altos de ONe para niños asmáticos y atópicos en conjunto, con respecto a lo esperado por el impacto del asma y atopia por separado. Estas diferencias se han visto incluso en población de niños bajo tratamiento con corticoides [9][10][11] . No son claras las razones para no haber observado diferencias en niveles de ONe según asma y atopia en nuestro estudio.…”
Section: Discussionunclassified
See 1 more Smart Citation